2011
DOI: 10.1186/1748-5908-6-35
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between basic science and clinical practice: The role of organizations in addressing clinician barriers

Abstract: BackgroundNew National Institutes of Health policies call for expansion of practice-based research to improve the clinical research enterprise and facilitate dissemination of evidence-based medicine.ObjectiveThis paper describes organizational strategies that influence clinicians' decisions to participate in clinical research.DesignWe reviewed the literature and interviewed over 200 clinicians and stakeholders.ResultsThe most common barriers to community clinician participation in clinical research relate to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Although the field of implementation science strives to address the recognised gap between knowledge generated in clinical trials and routine clinical practice,1 2 research has demonstrated significant delays in the diffusion and adoption of effective, evidence-based clinical practices 3 4. Closing this gap still remains a challenge for many health systems.…”
Section: Introductionmentioning
confidence: 99%
“…Although the field of implementation science strives to address the recognised gap between knowledge generated in clinical trials and routine clinical practice,1 2 research has demonstrated significant delays in the diffusion and adoption of effective, evidence-based clinical practices 3 4. Closing this gap still remains a challenge for many health systems.…”
Section: Introductionmentioning
confidence: 99%
“…10,90,91 On the other hand, elements that foster effective translation of best evidence into daily practice are influenced by nurses' understanding and believing that EBP improves patient care outcomes, clinical leaders' modeling EBP in daily practice, and a culture that supports practice change based on best evidence. 10,11 It is time to change the culture in our critical care units to one that embraces the translation of evidence into daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…2 This translational gap – the time between identifying effective procedures or care protocols and the adoption and sustained use of that information in routine practice - consists of many barriers. 3,4, 5 For example, it has been documented that passive dissemination of knowledge (i.e. solely through publications) is unlikely to substantially change professional behavior.…”
Section: Introductionmentioning
confidence: 99%